The next frontier in lung development and regeneration research: harnessing iPSC models to illuminate notch signaling pathways - Song, Yuetong; Yang, Sha; Lam, Timothy; Quach, Henry T.; Yang, Jielin; Salih, Rasha; Wong, Amy P. (Frontiers in Cell and Developmental Biology, 2025)
The respiratory system relies on a diverse repertoire of epithelial cell types to ensure efficient air conduction and gas exchange. This cellular heterogeneity arises through tightly coordinated intercellular signaling events that extend from embryonic development into the postnatal period. Among the key regulatory pathways, Notch signaling plays an integral role in guiding cell fate determination, proliferation, and differentiation. It is indispensable for the proper formation, maintenance, and repair of the airway epithelium. This review examines the broad influence of Notch signaling on mammalian airway epithelial biology and highlights unresolved questions—particularly those specific to human lung development—where human induced pluripotent stem cell–derived models offer promising tools to bridge existing knowledge gaps.